PENGGUNAAN MEDIA ANIMASI TULISAN TANGAN UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI PADA MAHASISWA - Rini Sri Indriani; Yuli Mulyawati; Mira Mirawati (Universitas Pakuan, 2020)
USE OF HAND WRITING ANIMATION MEDIA TO IMPROVE WRITING SKILLS DESCRIPTION OF DESCRIPTION IN STUDENTSOne of the functions of the Indonesian Language and Literature Learning course in general is as a means of increasing knowledge and skills in Indonesian language to gain and develop science, technology, and art. This research was conducted on November 20, 2019 in Class 5D PGSD FKIP UNPAK with a total of 26 people consisting of 3 men and 23 women, Odd Academic Year 2019-2020. The results of research that researchers do are processed using descriptive statistics. Based on research conducted on the assessment of descriptive essays using Handwriting Animation media, the recapitulation results are obtained as follows: For the content or ideas expressed, obtained a score of 77 with very good criteria. Content organizations score 78 with Very Good criteria. Grammar scores 78 with Very Good criteria. Style: choice of structure and vocabulary scored 76 with Very Good criteria. Results of recapitulation Assessment of the use of animated media Handwriting on the making of descriptive essays for indicators of the suitability of the material 100% of students are in conformity so that the criteria are Very Good ,. The duration of making animation 100% in accordance with the time that has been set is a maximum of 30 minutes so the criteria are Very Good. The beauty of the appearance in Handwritten animation that has been made is only 75% with the criteria Very Good. Posts that are made get 100% accordingly so that the criteria are very good..